Faktor-Faktor yang Berhubungan dengan Kepuasan Pasien HIV dan AIDS Terhadap Pelayanan Gizi Selama Rawat Inap - , NUR SHOLIKHAH P S, dr. Yanri Wijayanti Subronto, Ph.D, SpPD ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Backgroud: Nutrition care is essential health services, especially for patient with HIV and AIDS. Therefore, nutrition care should be improved to provide satisfaction to the patient. Patient satisfaction was considered predictor and utilization treatment to improve the quality of life. Objective: To identify factors related to patient satisfaction with HIV and AIDS towards nutrition care in hospital. Methods: This study was a mixed method, there were phenomenology qualitative and cross sectional design. Subject of the study were as many 33 patients with HIV and AIDS in HIV referral Hospital. Methods of data collection was done by using the ServQualâs questionnaire that was modified for nutrition care, and guideline of indepth interview. Data were collected from October 2012 to May 2013. Relationshipâs analysis among variables used chi- square test and logistic regression test. Data analysis was performed by using statistical analysis software. Result: The results showed that the level of patient satisfaction was good enough amounting 66,67% (n=22) of the 33 respondents.This was confirmed by the results of in-depth interview with the majority of patients were satisfied with nutrition care. Statistical showed that there was no correlation between characteristics of respondents, administrative factors, tangible, reliability, and responsiveness with patient satisfaction (p>0,05). Whereas, assurance and empathy showed correlation with patient satisfaction (p<0,05). Conclusion: Factors related to patient satisfaction with HIV and AIDS towards nutrition care in hospital was the assurance and empathy.